2020
DOI: 10.11606/s1518-8787.2020054002481
|View full text |Cite
|
Sign up to set email alerts
|

A brief-review of the risk factors for covid-19 severity

Abstract: The World Health Organization has emphasized that one of the most important questions to address regarding the covid-19 pandemic is to understand risk factors for disease severity. We conducted a brief review that synthesizes the available evidence and provides a judgment on the consistency of the association between risk factors and a composite end-point of severe-fatal covid-19. Additionally, we also conducted a comparability analysis of risk factors across 17 studies. We found evidence supporting a total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
174
2
17

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(222 citation statements)
references
References 20 publications
29
174
2
17
Order By: Relevance
“…Some situations involved in the pathogenesis of late-onset preeclampsia, as predisposing cardiovascular or metabolic factors for endothelial dysfunction, or a systemic hyperinflammatory status have also been described as triggers of COVID-19 severity [15]. Among the presenting symptoms and complementary tests related to a higher risk of hospitalization in our study, fever and CRP have been previously described to have a high consistency of association with COVID-19 severe forms [16]. Regarding dyspnea, previous publications have suggested its presence in 60-70% of healthy pregnant women, therefore distinguish whether it is a physiological event or a pathological finding in these patients may be essential in the severity assessment [17].…”
Section: Discussionsupporting
confidence: 59%
“…Some situations involved in the pathogenesis of late-onset preeclampsia, as predisposing cardiovascular or metabolic factors for endothelial dysfunction, or a systemic hyperinflammatory status have also been described as triggers of COVID-19 severity [15]. Among the presenting symptoms and complementary tests related to a higher risk of hospitalization in our study, fever and CRP have been previously described to have a high consistency of association with COVID-19 severe forms [16]. Regarding dyspnea, previous publications have suggested its presence in 60-70% of healthy pregnant women, therefore distinguish whether it is a physiological event or a pathological finding in these patients may be essential in the severity assessment [17].…”
Section: Discussionsupporting
confidence: 59%
“…Identifying the death risk associated with critically ill patients early and giving these patients priority treatment in a timely manner are particularly important in global health emergencies. Studies have shown that a total of 60 predictors can assess the severity of COVID-19, of which 7 factors are considered to be highly correlated and consistent, including SOFA score, age, D-dimer, hs-CRP, body temperature, albumin and diabetes [13] . The results of this study revealed that SOFA score, age, CKD, CLD1, CLD2, cystatin C, hs-CRP, CK, CK-MB and other factors were independent risk factors for in-hospital death, which was similar to the results of the above study.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen modulates the immune response and contributes to the production of more antibodies. 7 On the other hand, men have less antibodies that decrease the expression of IL-6, which is linked to deregulation of the immune system and lung damage. Likewise, men have higher concentrations of angiotensin-converting enzyme 2 (ACE2) in the alveolar membrane of the lungs through which SARS-CoV-2 enters and infects its host.…”
Section: Discussionmentioning
confidence: 99%
“…4 People with a previous diagnosis of non-communicable diseases (NCDs) such as high blood pressure (HBP), type 2 diabetes (T2D), cardiovascular disease (CVD), and chronic obstructive pulmonary disease (COPD), [5][6] as well as those who are older or men, are more likely to develop serious conditions of COVID- 19 or die from this cause. 7 In China, the fatality rate (number of deaths per 100 infected) for COVID-19 was 2.3%. However, it was 6.0% for people with hypertension, 7.3% for adults with diabetes and 10.5% for people with cardiovascular disease 10.5%.…”
Section: Introductionmentioning
confidence: 99%